The South Beach diet : good fats good carbs guide - Agatston, Arthur.
You don't have to give up fats or carbs--you just need to choose the right ones. All fats and carbohydrates aren't created equal. The good kinds nourish your body as they help you lose weight. The bad kinds--found in sugary, fatty foods like doughnuts, snack foods, and fast-food meals--damage your body’s ability to burn off what you eat. Worse, eating them actually triggers cravings and makes you even hungrier!